2021
DOI: 10.1111/apps.12356
|View full text |Cite
|
Sign up to set email alerts
|

Are adaptable employees more likely to stay? Boundaryless careers and career ecosystem perspectives on career adaptability and turnover

Abstract: Employees with higher career adaptability (CA) have been shown in previous research to be more likely to build high‐quality social exchange relations with current employers, thereby displaying a lower intention to leave. Based on boundaryless careers and career ecosystem perspectives, this study aimed to challenge and enrich the extant understanding of this important question by examining the mixed effects of CA on turnover behavior. Results from a three‐wave survey study with 179 Chinese employees show that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 78 publications
1
13
0
Order By: Relevance
“…They would search for external opportunities to keep flexibility in their careers and perceive high external marketability (Spurk et al, 2016). Keeping at current jobs would make people feel that they are deprived of external potential (Wang et al, 2021). In this sense, career adaptability might harm interpersonal relationships and proactive work behaviour, because people might not want to devote themselves to the current organization.…”
Section: T a B L E 4 Conditional Indirect Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…They would search for external opportunities to keep flexibility in their careers and perceive high external marketability (Spurk et al, 2016). Keeping at current jobs would make people feel that they are deprived of external potential (Wang et al, 2021). In this sense, career adaptability might harm interpersonal relationships and proactive work behaviour, because people might not want to devote themselves to the current organization.…”
Section: T a B L E 4 Conditional Indirect Effectsmentioning
confidence: 99%
“…Spurk et al (2016) showed that career adaptability also improved perceived internal marketability. Wang et al (2021) showed that career adaptability reduced turnover behaviour through affective commitment. Meta-analyses showed a significant negative relationship between career adaptability and turnover intention (Rudolph et al, 2017).…”
Section: T a B L E 4 Conditional Indirect Effectsmentioning
confidence: 99%
“…The boundaryless careera career choice that "enables individuals to continuously engage in the cycle of learning and adaptation" (Wang et al, 2022(Wang et al, , p. 1327)has gained a new focus due to career adaptability. Other similar career approaches have also emerged, including the self-directed career and the protean career (Hall, 2002).…”
Section: Literature Review 21 Career Attitudes and Behaviorsmentioning
confidence: 99%
“…This theory brings together different actors that interact and are inter‐related, each one of them influences the path, progress and direction of other actors (Bhaskar et al, 2022). Empirical studies indicate the usefulness of the theory in terms of explicating career adaptation processes (Wang et al, 2022). Specific studies looked at the transition from higher education to the labor market (Donald et al, 2021; Healy et al, 2022).…”
Section: Theoretical Frameworkmentioning
confidence: 99%